Sistem Pendukung Keputusan Dengan Metode Simple Additive Weighting (SAW) Dalam Kelayakan Pemberian Kredit Bank - Puji Astuti (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract— Credit is a provider of bills or equivalent, based on a loan agreement or agreement between the Bank and another party that requires the borrower to repay the debt after a certain period of time with the amount of interest, compensation or profit sharing. Decision Support System is given to provide alternative solutions to the Bank or provider of loan money to who is entitled to credit. By using the Simple Additive Weight (SAW) method, the meal will be known to be feasible or not, smooth or not smooth during the payment process. The SAW method uses the criteria to get the best alternative results that are eligible for credit. The SAW method uses the matrix normalization process as a calculation with the results of a comparison scale with all available alternative ratings. Keyword: SAW, DSS, Credit